To solve for the value of x in the equation x - 7 = 1, we need to add 7 to both sides of the equation.
By adding 7 to both sides, we get:
x - 7 + 7 = 1 + 7
Simplifying the equation, we have:
x = 8
Therefore, the value of x is 8.
what number should be added to both sides of the equation x-7=1 to solve the value of x
25 answers
what number should be added to both sides of the equation x - 7/8 = -5
To solve the equation x - 7/8 = -5 and find the value of x, we need to add 7/8 to both sides of the equation.
By adding 7/8 to both sides, we get:
x - 7/8 + 7/8 = -5 + 7/8
Simplifying the equation, we have:
x = -5 + 7/8
To add -5 and 7/8, we need to find a common denominator. The denominator of 8 is already common, so we have:
x = -5(8/8) + 7/8
x = -40/8 + 7/8
To add the fractions, the denominators must be the same. In this case, they are already the same, so we can add the numerators:
x = (-40 + 7)/8
x = -33/8
Therefore, the value of x is -33/8.
By adding 7/8 to both sides, we get:
x - 7/8 + 7/8 = -5 + 7/8
Simplifying the equation, we have:
x = -5 + 7/8
To add -5 and 7/8, we need to find a common denominator. The denominator of 8 is already common, so we have:
x = -5(8/8) + 7/8
x = -40/8 + 7/8
To add the fractions, the denominators must be the same. In this case, they are already the same, so we can add the numerators:
x = (-40 + 7)/8
x = -33/8
Therefore, the value of x is -33/8.
what number should be added to both sides of the equation x - 7/8 = -5 to find the value of x
To solve the equation x - 7/8 = -5 and find the value of x, we need to add 7/8 to both sides of the equation.
By adding 7/8 to both sides, we get:
x - 7/8 + 7/8 = -5 + 7/8
Simplifying the equation, we have:
x = -5 + 7/8
To combine the terms on the right side of the equation, we need to find a common denominator. The denominator of 8 is already common, so we have:
x = -5(8/8) + 7/8
x = -40/8 + 7/8
To add the fractions, the denominators remain the same. Therefore, we can simply add the numerators:
x = (-40 + 7)/8
x = -33/8
Therefore, the value of x is -33/8.
By adding 7/8 to both sides, we get:
x - 7/8 + 7/8 = -5 + 7/8
Simplifying the equation, we have:
x = -5 + 7/8
To combine the terms on the right side of the equation, we need to find a common denominator. The denominator of 8 is already common, so we have:
x = -5(8/8) + 7/8
x = -40/8 + 7/8
To add the fractions, the denominators remain the same. Therefore, we can simply add the numerators:
x = (-40 + 7)/8
x = -33/8
Therefore, the value of x is -33/8.
What is the value of x in the equation x + 0.97 = -2
To solve for the value of x in the equation x + 0.97 = -2, we need to isolate x by subtracting 0.97 from both sides of the equation:
x + 0.97 - 0.97 = -2 - 0.97
Simplifying the equation, we have:
x = -2 - 0.97
To subtract the numbers on the right side, we can find a common denominator. The denominator of 1 in 0.97 can be written as 100/100. So, we have:
x = -2 - 0.97(100/100)
x = -2 - 97/100
Next, to combine the terms on the right side of the equation, we need a common denominator. The denominator of 100 is already common, so we can simply add the numerators:
x = (-2 * 100 - 97) / 100
x = (-200 - 97) / 100
x = -297 / 100
Therefore, the value of x is -297/100.
x + 0.97 - 0.97 = -2 - 0.97
Simplifying the equation, we have:
x = -2 - 0.97
To subtract the numbers on the right side, we can find a common denominator. The denominator of 1 in 0.97 can be written as 100/100. So, we have:
x = -2 - 0.97(100/100)
x = -2 - 97/100
Next, to combine the terms on the right side of the equation, we need a common denominator. The denominator of 100 is already common, so we can simply add the numerators:
x = (-2 * 100 - 97) / 100
x = (-200 - 97) / 100
x = -297 / 100
Therefore, the value of x is -297/100.
What is the solution of the equation x - 9/4 = -3/8?
To solve the equation x - 9/4 = -3/8, we need to isolate x.
First, let's add 9/4 to both sides of the equation:
x - 9/4 + 9/4 = -3/8 + 9/4
This simplifies to:
x = -3/8 + 9/4
To add these fractions, we need a common denominator. The lowest common multiple of 8 and 4 is 8, so we can rewrite the fractions with the common denominator of 8:
x = -3/8 + 9/4
x = -3/8 + 18/8
x = (18 - 3)/8
x = 15/8
Therefore, the solution to the equation x - 9/4 = -3/8 is x = 15/8.
First, let's add 9/4 to both sides of the equation:
x - 9/4 + 9/4 = -3/8 + 9/4
This simplifies to:
x = -3/8 + 9/4
To add these fractions, we need a common denominator. The lowest common multiple of 8 and 4 is 8, so we can rewrite the fractions with the common denominator of 8:
x = -3/8 + 9/4
x = -3/8 + 18/8
x = (18 - 3)/8
x = 15/8
Therefore, the solution to the equation x - 9/4 = -3/8 is x = 15/8.
what number should be added to both sides of the equation x + 11 = -17 to solve the value of x
To solve for the value of x in the equation x + 11 = -17, we need to isolate x by subtracting 11 from both sides of the equation.
By subtracting 11 from both sides, we get:
x + 11 - 11 = -17 - 11
Simplifying the equation, we have:
x = -17 - 11
To add -17 and -11, we simply add the two numbers together:
x = -28
Therefore, the value of x is -28.
By subtracting 11 from both sides, we get:
x + 11 - 11 = -17 - 11
Simplifying the equation, we have:
x = -17 - 11
To add -17 and -11, we simply add the two numbers together:
x = -28
Therefore, the value of x is -28.
Which answer
Subtract 17
Add 11
Subtract 11
Add 17
Subtract 17
Add 11
Subtract 11
Add 17
The correct answer is to subtract 11 from both sides of the equation.
What is the solution of the equation x + 23 = 9
To solve the equation x + 23 = 9, we need to isolate x by subtracting 23 from both sides of the equation.
By subtracting 23 from both sides, we get:
x + 23 - 23 = 9 - 23
Simplifying the equation, we have:
x = -14
Therefore, the solution to the equation x + 23 = 9 is x = -14.
By subtracting 23 from both sides, we get:
x + 23 - 23 = 9 - 23
Simplifying the equation, we have:
x = -14
Therefore, the solution to the equation x + 23 = 9 is x = -14.
Which of the following equations has a solution of -8?
To determine which equation has a solution of -8, we need to evaluate each equation using -8 as the value of x.
1) x + 5 = -3
Using -8 as the value of x:
-8 + 5 = -3
-3 = -3
The equation x + 5 = -3 is not satisfied when x = -8.
2) 2x - 6 = -22
Using -8 as the value of x:
2(-8) - 6 = -22
-16 - 6 = -22
-22 = -22
The equation 2x - 6 = -22 is satisfied when x = -8.
3) 4x + 10 = 2
Using -8 as the value of x:
4(-8) + 10 = 2
-32 + 10 = 2
-22 = 2
The equation 4x + 10 = 2 is not satisfied when x = -8.
Based on our evaluations, the equation 2x - 6 = -22 has a solution of -8.
1) x + 5 = -3
Using -8 as the value of x:
-8 + 5 = -3
-3 = -3
The equation x + 5 = -3 is not satisfied when x = -8.
2) 2x - 6 = -22
Using -8 as the value of x:
2(-8) - 6 = -22
-16 - 6 = -22
-22 = -22
The equation 2x - 6 = -22 is satisfied when x = -8.
3) 4x + 10 = 2
Using -8 as the value of x:
4(-8) + 10 = 2
-32 + 10 = 2
-22 = 2
The equation 4x + 10 = 2 is not satisfied when x = -8.
Based on our evaluations, the equation 2x - 6 = -22 has a solution of -8.
Which answer
x + 3 = -11
x - 8 = 0
x - 10 = 2
x - 4 = -12
x + 3 = -11
x - 8 = 0
x - 10 = 2
x - 4 = -12
The equation that has a solution of -8 is:
x + 3 = -11
x + 3 = -11
Which of the following should be done to both sides of the equation x - 3.41 = -19 to solve the value of x
To solve for the value of x in the equation x - 3.41 = -19, we need to add 3.41 to both sides of the equation.
By adding 3.41 to both sides, we get:
x - 3.41 + 3.41 = -19 + 3.41
Simplifying the equation, we have:
x = -19 + 3.41
To add -19 and 3.41, we simply add the two numbers together:
x = -15.59
Therefore, the value of x is -15.59.
By adding 3.41 to both sides, we get:
x - 3.41 + 3.41 = -19 + 3.41
Simplifying the equation, we have:
x = -19 + 3.41
To add -19 and 3.41, we simply add the two numbers together:
x = -15.59
Therefore, the value of x is -15.59.
Which answer
Subtract 19
Add 3.41
Subtract 3.41
Add 19
Subtract 19
Add 3.41
Subtract 3.41
Add 19
The correct answer is to add 3.41 to both sides of the equation.
Which of the following equations has a solution of -1/2 (1 point)
x + 1 = 1/2
x + 1/2 = -1
x - 1/2 = 1
x - 1 = -1/2
x + 1 = 1/2
x + 1/2 = -1
x - 1/2 = 1
x - 1 = -1/2
To determine which equation has a solution of -1/2, we will evaluate each equation using -1/2 as the value of x.
1) x + 1 = 1/2
Using x = -1/2:
(-1/2) + 1 = 1/2
1/2 = 1/2
The equation x + 1 = 1/2 is satisfied when x = -1/2.
2) x + 1/2 = -1
Using x = -1/2:
(-1/2) + 1/2 = -1
0 = -1
The equation x + 1/2 = -1 is not satisfied when x = -1/2.
3) x - 1/2 = 1
Using x = -1/2:
(-1/2) - 1/2 = 1
-1 = 1
The equation x - 1/2 = 1 is not satisfied when x = -1/2.
4) x - 1 = -1/2
Using x = -1/2:
(-1/2) - 1 = -1/2
-1.5 = -1/2
The equation x - 1 = -1/2 is not satisfied when x = -1/2.
Based on our evaluations, the only equation that has a solution of -1/2 is x + 1 = 1/2.
1) x + 1 = 1/2
Using x = -1/2:
(-1/2) + 1 = 1/2
1/2 = 1/2
The equation x + 1 = 1/2 is satisfied when x = -1/2.
2) x + 1/2 = -1
Using x = -1/2:
(-1/2) + 1/2 = -1
0 = -1
The equation x + 1/2 = -1 is not satisfied when x = -1/2.
3) x - 1/2 = 1
Using x = -1/2:
(-1/2) - 1/2 = 1
-1 = 1
The equation x - 1/2 = 1 is not satisfied when x = -1/2.
4) x - 1 = -1/2
Using x = -1/2:
(-1/2) - 1 = -1/2
-1.5 = -1/2
The equation x - 1 = -1/2 is not satisfied when x = -1/2.
Based on our evaluations, the only equation that has a solution of -1/2 is x + 1 = 1/2.